The effects of normal and interrupted sleep combined with acute caffeine supplementation on some immune system indices and anaerobic power in male athletes - Mohammad hossein Hashemzadeh; Farhad Rahmaninia; Payam Saidie (Shahid Beheshti University, 2024)
Background and Purpose: Adequate sleep is recognized as a fundamental factor in enhancing athletic performance. Studies have shown that poor sleep can lead to decreased anaerobic power and increased risk of diseases. Additionally, caffeine consumption, as one of the popular sports supplements, can directly or indirectly affect the immune system through its impact on sleep and rest, and also result in positive effects on performance. In the current study, the effects of normal and interrupted sleep combined with acute caffeine supplementation on some immune system indices and anaerobic power in male athletes were examined.Materials and Methods: This semi-experimental study was conducted using a randomized design. Fourteen male athletes (mean±SD; age, 22.92±1.32 years; height, 176.4±4.38 cm; weight, 71.42±9.65 kg) participated in this study. Participants were randomly and equally assigned to 2 groups and 2 sessions: 1) normal sleep, caffeine/placebo (NSP/NSC) and 2) Interrupted sleep, caffeine/placebo (ISP/ISC). The supplement group consumed 6 mg of caffeine per kilogram of body weight, while the placebo group consumed chickpea flour. To assess anaerobic power, a Monark cycle ergometer test was applied with 20 seconds of cycling followed by 20 seconds of rest, immediately followed by 12 sets of 4-second cycling with 10-second rests. Blood samples were taken at four time points: 8 AM (baseline), 60 minutes after supplementation, 5 minutes post-test, and 360 minutes post-test.Results: Five minutes after the test, platelet to lymphocyte ratio (PLR), neutrophil to lymphocyte ratio (NLR), and systemic immune-inflammation (SII) values showed a significant decrease in normal sleep and caffeine conditions compared to interrupted sleep and placebo conditions. Whith blood cells (WBC) values in normal sleep and placebo conditions demonstrated a significant (p<0.05) increase compared to other conditions at 360 minutes post-test. Additionally, at 360 minutes post-test, NLR and SII values in interrupted sleep and caffeine conditions showed a significant increase compared to normal sleep and caffeine conditions (p<0.05). Caffeine supplementation significantly increased NLR and SII values in interrupted sleep and caffeine conditions compared to normal sleep and placebo conditions (p<0.05). Caffeine consumption led to a significant increase in peak power in the normal sleep group compared to other conditions (p<0.05).Conclusion: The results indicated that sleep deprivation negatively impacts immune system indicators, and caffeine supplementation after sleep deprivation improves some immune markers. Although the ergogenic effects of caffeine were confirmed under normal sleep conditions, the lack of enhancement in anaerobic performance with caffeine supplementation during sleep deprivation suggests a need for further research on the effects of different dosages of caffeine supplementation on anaerobic performance. Therefore, considering the improvement in immune function markers under sleep deprivation with caffeine supplementation, even without enhancing anaerobic performance, and the fact that sleep deprivation strongly activates the body's inflammatory signaling network, the use of this supplement can be recommended for athletes in conditions of sleep deprivation and before intense activities.